2020
DOI: 10.1007/s00107-020-01572-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of northern hardwoods in glued-laminated timber: a study of bondline shear strength and resistance to moisture

Abstract: The growing demand for engineered wood products in the construction sector has resulted in the diversification of the product offer. Used marginally in structural products in North America, northern hardwoods are now attracting a growing interest from industry and policy makers because of their outstanding strength as well as their high availability and distinctive appearance. Currently, there is no standard in Canada governing the use of hardwoods in the manufacturing of glued-laminated timber. As part of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Several studies showed that MUF bonded hardwood produced more than 2 times lower delamination compared to PUR bonding [30][31][32]. A recent study on white oak, white ash, yellow birch, and birch glulam specimens bonded with melamine-formaldehyde (MF) and two-component PUR (2C-PUR) showed that the loss of strength induced by the moisture and differential wood swelling caused by the vacuum-pressure cycle was considerable (50%), especially for high-density specimens bonded with 2C-PUR adhesive (around 60% reduction) [32]. Knorz et al [30] compared the bonding quality of glulam made of ash with various adhesives i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that MUF bonded hardwood produced more than 2 times lower delamination compared to PUR bonding [30][31][32]. A recent study on white oak, white ash, yellow birch, and birch glulam specimens bonded with melamine-formaldehyde (MF) and two-component PUR (2C-PUR) showed that the loss of strength induced by the moisture and differential wood swelling caused by the vacuum-pressure cycle was considerable (50%), especially for high-density specimens bonded with 2C-PUR adhesive (around 60% reduction) [32]. Knorz et al [30] compared the bonding quality of glulam made of ash with various adhesives i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Another hardwood that is increasing in its use in glued laminated timber is oak. This strong but brittle hardwood is also known for its increased content of extractive substances in the wood and specific behaviour at increased humidity [8]. Softwoods, such as poplar or alder, are also of considerable interest [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the currently growing demand for engineered wood products is largely attributable to their outstanding ecological performance. The substitution of materials having a larger ecological footprint, such as steel and concrete, by structural engineered wood products like laminated wood has proven to be effective in minimizing the environmental impacts of the building sector [1]. Furthermore, laminated wood is a material of a great aesthetic value, with various applications in the field of building components, such as doors and windows, and in the field of timber structures of big and small spans [2,3].…”
Section: Introductionmentioning
confidence: 99%